Effectiveness of Communication Strategy Implementation in Covid-19 Response in Aceh Province Through Islamic Education - Nadar Putra; Syukur Kholil; Abdullah Abdullah; Ahmad Tamrin Sikumbang (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The position of Aceh Province is ranked sixth lowest positive for Covid-19 out of 34 other provinces in Indonesia and third out of 10 provinces in Sumatra in terms of the number of additional positive daily cases of Covid-19, the accumulated positive number of Covid-19 and the recovery rate of patients who are positive for Covid-19. These figures occurred after Aceh Province experienced three waves of Covid-19 spread, namely the first wave that occurred since the establishment of the Emergency Response period by the Central Government through BNPB, namely January 28, 2020 and lasted until April 23, 2020. The purpose of this study is to see the effectiveness of Islamic communication strategies in overcoming covid-19 in Aceh Province, one of which is through Islamic Education. This research is designed as a Descriptive Qualitative research with a phenomenological approach, which is a study that describes in detail the results of in-dept interviews with informants and observations of research subjects about various data related to phenomena that appear and do not appear to be oral words, attitudes, behaviors and facial expressions, as primary data. The results of this study show effectiveness in overcoming Covid-19 with one of its strategies through guidance and direction counseling and guidance Islamic education